Surgery for late type Ia/IIIb endoleak from a fabric tear and stent fracture of AFX2 stent graft - Simone Cuozzo, MD; Francesca Miceli, MD; Antonio Marzano, MD; Ombretta Martinelli, MD; Roberto Gattuso, MD, FEBVS; Enrico Sbarigia, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2022)
Technical improvements and labeling updates of the AFX2 stent graft (Endologix Inc, Irvine, CA) seemed to have solved the known issues of its previous generation (AFX Strata). Although most endograft failures after endovascular abdominal aortic aneurysm repair will be managed endovascularly, a small subset of patients will still require secondary open conversion. Partial or complete endograft removal can be required, mainly dependent on the characteristics of the stent graft previously placed. We have report a case of secondary open conversion for late type Ia/IIIb endoleak due to stent fracture and fabric tear of the AFX2 stent graft 3 years after endovascular abdominal aortic aneurysm repair.